Developing a collaboration network framework to facilitate geospatial data access and exchange in the context of National Geospatial Data Infrastructure (NGDI) - Odeyemi, Chris (School of Architecture, Planning and Geomatics, 2026)
National Geospatial Data Infrastructures (NGDIs) provide holistic frameworks with several technological components that address and overcome geospatial access and exchange issues. The components of any NGDI area include geospatial data, people, access networks, policies, and standards that aim to facilitate geospatial data management. Even though geospatial datasets are becoming more available in most African countries, access and exchange is still challenging. In Nigeria, most Geospatial Information (GI) stakeholders (producers, providers, and users) acquire and produce the same types of geospatial datasets, which are fragmented within the different databases across the nation, thus making them redundant. The challenges to coordinating geospatial data access and exchange using collaboration networks have not been investigated thoroughly. Access to geospatial datasets remains a critical developmental enabler in Africa, which is the overarching goal of any NGDI. It is, therefore, pertinent to investigate how civil society can easily and quickly access and exchange geospatial data in the context of NGDI for sustainable development. This research aims to develop a collaboration network framework to enable access and exchange of geospatial data between GI stakeholders to support the development and implementation. National Geospatial Data Infrastructure (NGDI). A mixed-method research approach is adopted for this research. It combines qualitative and quantitative analysis methods using survey questionnaires and semi-structured interviews to develop a generic collaborative network framework for geospatial access and exchange. The study further reveals that governance, policy, technology, culture, and economics can influence the administration of NGDI through collaboration networks in the country. The developed framework incorporates the five identified components of a collaboration network for geospatial spatial data access, sharing, and exchange as an administrative tool to overcome the challenges faced for further development and the implementation of NGDI in the country. An SDI-Readiness index status was computed for Nigeria to be 0.84 (84%). In a broad sense, the SDI-readiness index has improved compared to 0.58 (58%) computed in 2017, and any country with an index greater than 0.8 can be called a spatially enabled society. This study considered governance, policy, technology culture, economics, and communication as a significant aspect of understanding collaboration networks. The problem investigated in this research is to understand how these five components of a collaboration network can potentially contribute to the goals of development and implementation of NGDI, which requires formalizing a collaboration network between GI stakeholders for geospatial data access and exchange. This research proposed a collaboration network initiative as best practice for NGDI in Nigeria to facilitate geospatial access and exchange. NGDI development and implementation proposed here, through collaboration network, draws heavily on, one, SDI cookbook of the elements and status of SDI, and two the Implementation Guide of IGIF. Furthermore, this research integrated knowledge from geoinformation technology, business, and public administration to help develop the framework. The research has helped close a knowledge gap in that GI organizations to build collaboration networks for geospatial data access and exchange among Public Geospatial Information (GI) stakeholders. Further avenues of research address the need for monitoring the performance of collaboration networks, as it affects geospatial data sharing and exchange, the impact of Internet-of-Things (IoT) on NGDI, the influence of the private sector's on the development and implementation of NGDI, the integration of real-time sensor-based systems to NGDI and exploring the possibility of expanding collaboration network framework into developing a regional NGDI initiative.